2015
DOI: 10.1111/add.13081
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age differences in the early identification and treatment of alcohol use: a population‐based study of patients with alcoholic cirrhosis

Abstract: Aim: To estimate sex differences in healthcare utilisation among harmful/hazardous drinkers in the period before alcoholic cirrhosis diagnosis, and estimate sex differences in the extent to which alcohol use and brief alcohol interventions were documented for these individuals compared with a control cohort.Design: Retrospective study using linked UK general practice and hospital admissions data in England.Setting: Three hundred and fifty-seven general practitioner (GP) practices in England.Participants: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Poor recording of alcohol use has two major impacts: first and most importantly, patients may not be receiving appropriate interventions; and second, for researchers, poor recording may prohibit reliable studies of the impact of alcohol on health using these data. Indeed, some recent studies using alcohol data in a large UK-based primary care electronic health record database (Clinical Practice Research Datalink (CPRD)) have indicated that bias may have arisen due to poor recording of alcohol data 8 9. For researchers using the data it is important to know not just whether screening occurs but if there are particular subgroups more likely to be screened and to what extent alcohol codes used are meaningful reflections of actual alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…Poor recording of alcohol use has two major impacts: first and most importantly, patients may not be receiving appropriate interventions; and second, for researchers, poor recording may prohibit reliable studies of the impact of alcohol on health using these data. Indeed, some recent studies using alcohol data in a large UK-based primary care electronic health record database (Clinical Practice Research Datalink (CPRD)) have indicated that bias may have arisen due to poor recording of alcohol data 8 9. For researchers using the data it is important to know not just whether screening occurs but if there are particular subgroups more likely to be screened and to what extent alcohol codes used are meaningful reflections of actual alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining sex differences in internalizing psychopathology in individuals with AUDs may have important implications for treatment. For instance, studies have shown that males tend to be more evasive to seeking treatment and respond less favorably to treatment when compared to females (Jarvis, 1992;John, Alwyn, Hodgson, & Phillips, 2008;Otete, Orton, West, & Fleming, 2015). It is possible that, if males are drinking to relieve symptoms of anxiety, elevated levels of trait anxiety may play a unique role in influencing male's decreased likelihood to seek and respond favorably to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should assess contacts with obvious alcohol problems in primary care in addition to hospital contacts to compare where patients are most frequently seen with alcohol problems prior to diagnosis of alcoholic liver cirrhosis or alcoholic pancreatitis[ 18 , 20 , 42 ].…”
Section: Discussionmentioning
confidence: 99%